GRU4RecBE: A Hybrid Session-Based Movie Recommendation System (Student Abstract) - Potter, Michael; Liu, Hamlin; Lala, Yash; Loanzon, Christian; Sun, Yizhou (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
We present a novel movie recommendation system, GRU4RecBE, which extends the GRU4Rec architecture with rich item features extracted by the pre-trained BERT model. GRU4RecBE outperforms state-of-the-art session-based models over the benchmark MovieLens 1m and MovieLens 20m datasets.